Effects of carbon nanotubes on mechanical behavior of fiber reinforced composite under static loading - Kaboğlu, Cihan; Ferik, Erdem (WALTER DE GRUYTER GMBH, 2022)
The purpose of this research article is to show the effect of carbon nanotubes (CNTs) addition on fiber reinforced polymer matrix composites produced by the vacuum infusion method on tensile performance. In this study, glass, carbon, and fiber fabric reinforced polymer matrix composite plates were produced using glass, carbon and aramid fiber fabrics with the same weave type and similar areal density. Using the same production parameters, the composite plates reinforced with different fiber types were produced with CNTs addition by 0.5 wt% of total composite. Additionally, since it is thought that the effect of CNTs on performance in different fiber types may be different, hybrid fiber fabric reinforced composite plate material containing a composition of glass, carbon and fiber fabrics was produced and this material was produced with CNTs additive using the same production parameters as in previous fiber reinforced composite plate productions. In the study, composite plates with and without CNTs were produced in various compositions including glass, carbon, aramid, and hybrid fiber fabrics. As a result, CNTs reinforcement has increased the mechanical performance under tensile stress in glass, carbon, and hybrid reinforced fabric composite structures, but on aramid fiber, CNTs has decreased the performance.
Keywords: carbon nanotubes; composite; mechanical behavior; mechanics of materials; tensile strength